New Ways of Teaching Statics and Applied Structural Mechanics to Architects - Pospisil, Martin; Vavruskova, Marketa; Vertatova, Eva (Applied Mechanics and Materials, 2015)
Education of exact and technical subjects at traditional schools of architecture faces a difficult task to bring these disciplines to students of significantly lower technical perception, now. For this reason, at the Faculty of Architecture, Czech Technical University in Prague, a series of seminars containing the design of physical and virtual models completed by measuring and static calculations to supplement existing education of statics and applied structural mechanics is currently prepared.